Metafor Kerapan Sapi dalam Tata Kelola Perusahaan dari Sudut Pandang Teori Stewardship - Mohammad Baqir Ainun (LPPM Universitas Trunojoyo Madura, 2021)
This study aims to explain how kerapan sapi culture can describe corporate governance from the point of view of stewardship theory. Stewardship theory states that managers will carry out their duties and responsibilities in the interests of the organization and shareholders. In this theory, the manager will put aside his personal interests. Kerapan sapi is a Madurese culture that competes for the running speed of a pair of cows using pangonong and kaleles as a place for the tokang tongko' to stand to control the cows. Tokang tongko' is a party that has an important role in creating an effective and efficient running speed of Sapi Kerap in order to become a winner, just like a company manager who is the authorized party to manage the company effectively and efficiently in order to be able to compete with competitors. Tokang tongko' is assumed to have a trustworthy, honest, and responsible nature for the trust that has been given by the owner of the cow, which is often in accordance with the theory of stewardship. Tokang tongko' will take actions in accordance with the interests of sapi kerap owners, like a manager who carries out his duties and responsibilities in the interests of shareholders.